Seasonal Migration in the Aphid Genus Stomaphis (Hemiptera: Aphididae): Discovery of Host Alternation Between Woody Plants in Subfamily Lachninae. Issue 5 (30th September 2020) - Yamamoto, Tetsuya; Hattori, Mitsuru; Itino, Takao
Abstract: About 10% of aphid species show host alternation. These aphids migrate between primary and secondary host plant species in spring and autumn. Host alternation has not been observed in subfamily Lachninae, although it has been suggested on the basis of circumstantial evidence that Stomaphis japonica (Takahashi) may alternate its host between Quercus serrata (Murray) and Quercus acutissima (Carruth). However, a molecular phylogenetic study has indicated that the Stomaphis individuals feeding on these two plant species belong to two different lineages and aphids feeding on Q. acutissima and Pinus densiflora (Sieb. & Zucc.) belong to the same lineage. Here, we examined host alternation in Stomaphis species by comparing molecular phylogenetic identities, morphological features, and life cycles. The molecular analysis and morphological examination showed that aphids feeding on Q. acutissima were the same as those feeding on P. densiflora, whereas aphids feeding on Q. serrata were different from those feeding on Q. acutissima or on P. densiflora . Furthermore, winged aphids were observed on both Q. acutissima and P. densiflora in autumn, but we did not observe winged aphids on Q. serrata . These results indicate that Stomaphis (Walker) individuals feeding on Q. serrata and Q. acutissima belong to two species, one that feeds year-round on Q. serrata, and another, heteroecious species that feeds on P. densiflora as a primary host and on Q. acutissima as a secondary host. This study documents host alternation in subfamily Lachninae for the first time and discusses the acquisition of host alternation by Stomaphis from evolutionary and ecological perspectives.